2011
DOI: 10.1042/bst20110704
|View full text |Cite
|
Sign up to set email alerts
|

Combined anaerobic ammonium and methane oxidation for nitrogen and methane removal

Abstract: Anammox (anaerobic ammonium oxidation) is an environment-friendly and cost-efficient nitrogen-removal process currently applied to high-ammonium-loaded wastewaters such as anaerobic digester effluents. In these wastewaters, dissolved methane is also present and should be removed to prevent greenhouse gas emissions into the environment. Potentially, another recently discovered microbial pathway, n-damo (nitrite-dependent anaerobic methane oxidation) could be used for this purpose. In the present paper, we explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The correlated increases in the number of NC10 bacteria and the activity of methane oxidation indicated that NC10 bacteria were responsible for the everincreasing methane oxidation activity. The specific cell activity of the NC10 bacteria in the final marine denitrifying methanotrophic culture was 0.14 Ϯ 0.02 fmol CH 4 day Ϫ1 cell Ϫ1 , which corresponded to the previous measurements (0.09 to 0.34 fmol CH 4 day Ϫ1 cell Ϫ1 ) (8,26,38). Furthermore, the qPCR and FISH results showed that NC10 bacteria could grow in seawater media (20.5‰ of salinity) and that their apparent doubling times (38.7 to 48.9 days) were slightly longer than the doubling times previously observed in freshwater enrichment cultures (14 to 25 days) (3,29).…”
Section: Figsupporting
confidence: 55%
“…The correlated increases in the number of NC10 bacteria and the activity of methane oxidation indicated that NC10 bacteria were responsible for the everincreasing methane oxidation activity. The specific cell activity of the NC10 bacteria in the final marine denitrifying methanotrophic culture was 0.14 Ϯ 0.02 fmol CH 4 day Ϫ1 cell Ϫ1 , which corresponded to the previous measurements (0.09 to 0.34 fmol CH 4 day Ϫ1 cell Ϫ1 ) (8,26,38). Furthermore, the qPCR and FISH results showed that NC10 bacteria could grow in seawater media (20.5‰ of salinity) and that their apparent doubling times (38.7 to 48.9 days) were slightly longer than the doubling times previously observed in freshwater enrichment cultures (14 to 25 days) (3,29).…”
Section: Figsupporting
confidence: 55%
“…S2), which was from the inoculum (Table S1) and the decomposition of organic matters. Since anaerobic ammonia oxidation (anammox) bacteria have a higher affinity for nitrite than n-damo bacteria (Luesken et al 2011a;Zhu et al 2011), anammox reaction might be significant in phase I, especially in the first 50 days. In short, n-damo bacteria had intense competitions from denitrifying and anammox bacteria when methanogenic sludge was selected as inoculum.…”
Section: Discussionmentioning
confidence: 99%
“…1), and these NC10 bacteria were physiologically active as denitrifying methanotrophs. Several enrichment cultures have indicated that group A members of the NC10 phylum perform AOM coupled to nitrite reduction45678910. Remarkably, the typical bacterium of the NC10 phylum, ‘ Candidatus Methylomirabilis oxyfera’ ( M. oxyfera ), utilizes oxygen produced from nitric oxide to intra-aerobically oxidize methane under anoxic conditions11.…”
mentioning
confidence: 99%